2022
DOI: 10.24911/biomedica/5-800
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing career choice in Generation Z: a study from students of private colleges in Lahore

Abstract: <p>Background and Objective: Choosing a career is a difficult decision, especially among young adults, which is influenced by many dynamics. Every adolescent faces the dilemma of choosing a career due to exposure to so many avenues in today&rsquo;s digitalized world. The objective of this study was to determine the factors influencing the career choices of Generation Z studying in different private colleges in Lahore city of Pakistan.</p> <p>Methods: It was a cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An article by Din et al (2022) explains how the most common parental influence on medical students' career choice was mutual agreement that a medical career would afford them a positive societal reputation and recognition. Similarly, it is found that role modelling of prestigious professions and higher salaries by parents influenced Generation Z's career choices significantly (Ahmed, 2022). Parents provide the context in which perceptions of career opportunities and occupational aspirations are formed through the process of socialization.…”
Section: Role Modellingmentioning
confidence: 98%
See 2 more Smart Citations
“…An article by Din et al (2022) explains how the most common parental influence on medical students' career choice was mutual agreement that a medical career would afford them a positive societal reputation and recognition. Similarly, it is found that role modelling of prestigious professions and higher salaries by parents influenced Generation Z's career choices significantly (Ahmed, 2022). Parents provide the context in which perceptions of career opportunities and occupational aspirations are formed through the process of socialization.…”
Section: Role Modellingmentioning
confidence: 98%
“…Related to parenting style is the function a parent serves in an individual's life. An article by Ahmed et al (2022) states that "parents are not just authority figures but friends, guides, and role models" (p. 232) as they provide financial and emotional support to their children. Finally, this research highly recommends "that parents do scaffolding for their children while choosing a career by keeping their interest as a priority which will be a source of job satisfaction and motivation for their children in the future" (p. 233).…”
Section: Parenting Stylementioning
confidence: 99%
See 1 more Smart Citation